LINGUISTIC AND CULTURAL CHARACTERISTICS OF ENGLISH AND UZBEK FOLK TALES - Shahnoza Tursunboyeva; Qazaqova Nozima Abdulboqiyevna (Western European Studies, 2024)
Linguistic, comparative, cognitive and practical linguistic and cultural issues specific to the fairy tale genre of English and Uzbek folklore are presented and explained in detail in the following article. Also, the significance and importance of the linguistic approach in the process of language analysis is emphasized. Problems related to language and culture, interdependence, communication and interaction of culture are cultural phenomena and have a specific scientific importance in linguistics. Therefore, it is natural that linguistic and cultural analysis occupies an important place in modern interdisciplinary research. It should be noted that language is not only a means of communication, but it is also considered as one of the most important cultural codes of a nation on a global scale.
Keywords: folklore; fairy tale; English; Uzbek